بنية الفضاء المكاني في رواية حكاية بحار لحنا مينه - هميسي، عبد الرشيد; عبادي، ايمان; كيرد، فائزة; عبيد، لاعج (University of Eloued جامعة الوادي, 2024)
يتمثل عنوان البحث في: بنية الفضاء المكاني في رواية حكاية بحار لحنا مينه. من أبرز ما جاء فيه: 1. تعدد واختلاف مصطلح الفضاء والمكان والحيز حسب تخصص ودراسة كل باحث. 2. تنوعت الأمكنة في الرواية بين المفتوحة والمغلقة، مثل: البحر، النهر، الشاطئ، الجبل، البيت، السفينة، المقهى... 3. هيمنة المكان المفتوح البحر على فضاء الرواية، فالرواية من البحر إلى البحر. 4. يعتبر الفضاء المكاني في الرواية عنصرا هاما لسيرورة الأحداث الروائية. The title of the research is ¨the structure of spatial space inthe novel the tale of a sailor by Hanna Minak, the most important thing it said: 1/ The many and different terms of space, place and space according to the specialization and study of each researcher. 2/ The places in the novel varied between open and closed, such as: the sea, the river, the beach, the mountain, the house, the ship, the café… 3/ The shape of the open place, the sea on the space of the novel, the nove lis from the sea and to the sea. 4/ Spatial space in the nove lis considered an important element in the process of novel events Le titre de la recherche est: la structure de l'espace spatial dans le roman le conte d'un marin de HANNA MINA. La chose la plus importante qu'il dit: *Les termes multiples et différents d'espace, de lieu et d'espace selon la spécialisation et l'étude de chaque chercheur. *Les lieux du roman variaient entre ouverts et fermés, tels que: la mer, la riviére, la plage, la montagne, les maisons, le bateau, le café… *La forme du lieu ouvert, la mer, sur l'éspace du roman, le roman va de la mer et vers la mer. *L'éspace spatial dans le roman est considéré comme un élément important dans le processus des événements romanesques.
813/ 031
Keywords: الرواية The novel الفضاء Outer space